2021
DOI: 10.1108/ci-02-2021-0027
|View full text |Cite
|
Sign up to set email alerts
|

Digital information technologies for prevention through design (PtD): a literature review and directions for future research

Abstract: Purpose With the rapid development of digital information and modelling software applications for construction, questions have arisen about their impact on construction safety. Meanwhile, recognition that designers can help reduce risks involved in construction, operation and maintenance via a prevention through design (PtD) approach (also known as design for safety) highlights the significance of digital technologies and tools to PtD. Thus, this paper aims to provide a systematic review of a wide range of dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…The implications here include the need for the quality of PtD education and training to meet the local needs of designers in terms of OHS and PtD. The education and training could include introducing designers to digital tools for PtD (Farghaly et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The implications here include the need for the quality of PtD education and training to meet the local needs of designers in terms of OHS and PtD. The education and training could include introducing designers to digital tools for PtD (Farghaly et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The implications here include the need for the quality of PtD education and training to meet the local needs of designers in terms of OHS and PtD. The education and training could include introducing designers to digital tools for PtD (Farghaly et al, 2021). For example, PtD inculcation in the education curricula can result in a shift from a high awareness level of PtD to a high level of knowledge of PtD.…”
Section: Study Implicationsmentioning
confidence: 99%
“…Poghosyan et al (2020) also developed a web-based tool for assessing the capability of design firms to implement DfS. Other digital tools for DfS are reported by Farghaly et al (2021). Studies have shown that client involvement and influence in DfS affect the concept's implementation (Goh and Chua, 2016;Tymvios and Gambatese, 2016).…”
Section: Design For Safety (Dfs)mentioning
confidence: 99%
“…Additionally, the digital tool facilitates the practical implementation of a PtD and SiD approach through developing an accessible knowledge-based system in a BIM environment. Traditionally, PtD relies on tacit knowledge combined with companies' policies and 2D drawings [27], while other forms of knowledge are not fully utilized, such as domain knowledge from regulations and guidelines, and explicit knowledge from government databases [76]. In fact, this lack of consolidated knowledge has been recognised as one of the challenges that BIM-based knowledge extraction and discovery faces [77].…”
Section: Discussion and Contributionmentioning
confidence: 99%